Pengaruh Viral Marketing dan Harga Tiket Terhadap Minat Berkunjung Masyarakat: Studi Kasus pada Objek Wisata Planet Waterboom Gorontalo - Allya Maulani Lumadja; Hapsawati Taan; Zulfia K. Abdussamad (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to determine how much influence viral marketing and ticket prices have on public interest in visiting (Case Study at Planet Waterboom Gorontalo Tourism Object). This type of research uses quantitative research methods. The sample of this study amounted to 100 respondents using non probability sampling technique and purposive sampling with the slovin formula. Data collection techniques in this study were carried out by questionnaire (questionnaire), observation and interview. Data analysis using multiple linear regression analysis. The results of the data that have been collected through the distribution of questionnaires have been tested with validity and reliability tests, classical assumption tests, multiple linear regression tests and hypothesis testing. Based on the research results of multiple linear regression analysis tests using the SPSS version 23 application, it shows that viral marketing variables have a negative and significant effect on visiting interest, ticket prices have a positive and significant effect on visiting interest. Viral marketing and ticket prices simultaneously affect public interest in visiting Planet Waterboom Gorontalo Tourism Object. The coefficient of determination shows an adjusted R square of 0.506. This shows that the influence of the independent variables, namely viral marketing and prices on the dependent variable of public interest in visiting the Planet Waterboom Gorontalo Tourism Object which can be explained by this equation model is 50,6%, while the remaining 49,4% is influenced by other variables not examined in this study.